Desarrollo de una herramienta para la generación de circuitos aritméticos aproximados - Hernández-Araya, Deykel (Instituto Tecnológico de Costa Rica, 2017)
Approximate computing is presented as a new paradigm that among many application layers, allows the design of energy e cient circuits. This taking advantage of that many applications have some tolerance to losses in the precision of their calculations, which allows to vary the structures and in turn the logical behavior of the arithmetic units that perform these computations. This project develops a tool that is capable of generating approximate arithmetic units hardware descriptions proposed in the community, in addition to execute various processes in external simulation and synthesis tools that provide relevant information for the design of a circuit in which is desired to introduce approximations. It is then as this document rst provides the characteristics of structure and logical behavior of the developed arithmetic units, followed by the process of design of the tool that includes the considerations and restrictions taken for the description in hardware, script writing towards external tools and structure programming. Finally, several of the cases are presented for which the tool can be used while checking the correct behavior of the described units.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2017.
Keywords: Circuitos aritméticos; Computación; Eficiencia energética; Sumadores aproximados; Multiplicadores aproximados; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electrical engineering